Pressure rise generation by the combustion of methane-air in a closed vessel - Aznam, Siti Nur Amalina (2015)
Experimental investigations were made to measure the variation of pressure development in a confined space at different equivalence ratio of methane-air combustion. A cylindrical vessel combustor that correspond to spherically expanding flame is used in this experiment. The experiment is subjected for only premixed methane-air mixture from five different equivalence ratio,Φ which are lean (0.7, 0.8), stoichiometric (1.0) and rich (1.2, 1.4). The instantaneous and maximum pressure were recorded using dynamic pressure transducer. The result of pressure profile at stoichiometry condition was compared with the previous work by other researcher. Based on the experimental investigation, the trend line of the buildup pressure profile at various equivalence ratio in this experiment is similar as obtain in previous work done in whichshows increment as the equivalence ratio moves from lean to slightly rich mixture. However it will eventually decrease when the mixture is too rich. The knowledge of maximum pressure can further be used to interpret the burning velocity of flame propagation.